A Randomised Controlled Trial Comparing the Effect of E-learning, with a Taught Workshop, on the Knowledge and Search Skills of Health Professionals - Nicola Pearce‐Smith (Evidence Based Library and Information Practice, 2006)
Objective The aim of the trial was to establish whether there is a significant difference in terms of knowledge and skills, between self-directed learning using a web-based resource, compared with a classroom based interactive workshop, for teaching health professionals how to search. The outcomes measured were knowledge of databases and study designs, and search skills. Methods The study design was a randomised controlled trial (RCT). 17 health professionals were randomised into one of two groups – one group (EG) received access to a search-skills web resource, and the other group received a search workshop (WG) taught by a librarian. Participants completed pre- and post-intervention tests involving multiple choice questions and practical searching using clinical scenarios. Results 9 WG and 6 EG participants completed both pre- and post-intervention tests. The test results were blindly marked using a score chart developed with two other librarians. For question formulation and devising a search strategy, all participants obtained a score that was the same or better after receiving the intervention (both WG and EG), but statistical analysis showed that the only significant outcomes were for the WG devising a search strategy (p=0.01) and preferring to search using MeSH after receiving the taught workshop (p=0.02). The Mann‐Whitney test showed there were no significant differences in any of the outcomes (p>0.05), between the WG and the EG. The statistical analyses must be viewed with caution due to the small sample size. Conclusion There were no significant differences in knowledge of databases and study design, or search skills, when the WG and the EG were compared. Although many participants obtained a score that was higher post‐intervention, only devising a search strategy and preferring to search using MeSH were statistically significant for the WG. The question of whether a taught workshop and an e-learning module are of equal effectiveness in teaching search skills, is an important one for health librarians involved in user education, and was a justifiable topic to propose and conduct research. The fact that the results are mainly inconclusive due to the small sample size is disappointing, but does not diminish the importance of conducting the study.